Local Wisdom, Green Open Space, and Fishermen Facilities in The Fishermen Village of Pantai Bahari - Nurul Nadjmi (Talenta Publisher, 2019)
Abstract. Pantai Bahari is one of the villages in Bangkala district, Jeneponto regency, South Sulawesi, Indonesia. Bangkala is a regions of Jeneponto regency, while Jeneponto is one of the regencies in South Sulawesi province that has the potential to develop seaweed because it has a coastline of more than 95 km with an area of ​​749.79 km2. One type of seaweed cultivated in Jeneponto is Eucheuma Cottonii. This type of seaweed has important economic value because it is material for crafts. Bangkala has an area of ​​121.82 km2, with a population of 46,932 people. The population density is 385/km2. The purpose of this study was to find out and analyze the fishermen settlement’s facilities in-depth along with the supporting infrastructures in Pantai Bahari village. The scope of the study is focused on settlement facilities and supporting facilities available in Pantai Bahari of Bangkala district, Jeneponto regency. Empathy is a process of understanding other people's feelings and feeling what others feel. The research method operative in this research was qualitative descriptive research. This qualitative research was done through a case study. The approach used was descriptive analytic approach. Direct observation was done to collect research data, and the results were then connected with the relevant theoretical studies. Based on the survey results conducted in Bangkala district of Jeneponto regency, the facilities are inadequately inadequate. This is due to the fact that SNI requirements and criteria have not been satisfied in building a good and adequate community facility. Keywords: Local Wisdom, Green Open Space Facilities, Fisherman Facilities, Pantai Bahari